Learning Life Skills through English Materials: Integrating Life Skills in English Pedagogy - Nurbatra, Laela Hikmah; Masyhud, Masyhud; Hartono, Hartono (ASEAN Journal of Community Engagement, 2022)
John Dewey once said that “education is not an affair of ‘telling’ and being told, but an active and constructive process.” Accordingly, pedagogical processes should not simply be conducted by traditional lecturing, but rather, they should be constructive processes that gradually build the meaning-making process of the children through their active participation. Therefore, this paper aims to suggest materials that integrate English learning and LSE that are specifically designed for Indonesian children. As a follow-up project from the previous program, the current community service focuses on the implementation of life skills education (LSE) by integrating LSE with English learning in non-formal educational institutions in Malang, East Indonesia with Taman Bacaan Masyarakat (TBM) Wacan as a partner. In doing so, the community service program conducted three phases of activities: planning, implementation, and evaluation in collaboration with Taman Bacaan Masyarakat Wacan and student volunteers. As a result, the community service has mapped out fourteen English materials units, which were embedded into LSE. The units have four major themes, namely, self-awareness and self-esteem, inter- and intrapersonal skill, problem-solving, and time and conflict management. Each of the major themes was then explored, emphasized in units that focused on different purposes and tried to evaluate whether the material fit the children’s context or needed more adjustment. However, due to limited time and resources, only one unit of materials was tried out to identify its usability and its flexibility. Based on the findings, it is recommended that English learning materials can be integrated with LSE to not only improve the children’s performance in using the language but also their broader life skills in this competitive era.